PROGRAMMING STRATEGY OF THE “SI OTAN” SERIAL AT TRANS 7 TV STATION - Adrianjara, Vayol Parama; Andrini, Susi (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2022)
This study aims to explain the Programming Strategy at the "Si Otan Di Trans7" program. The methodology used in this research is descriptive qualitative. Data was collected through observation, in-depth interviews, documentation and the internet to obtain in-depth and relevant information or data in research. While the theory used in this research is strategies & practices according to Sydney W, Head which states that in television broadcasting it is necessary to pay attention to five elements to carry out programming strategies, namely Compatibility, Habit formation, Control audience flow, Conservation of program resources and, Breadth of appeal. The results of this study showed significant results, that; Si Otan's programming strategy broadcast by TV-Trans7 station has implemented a programming strategy according to Sydney W. Head which includes these five elements.